Performances of broiler supplemented with antibiotic and Morinda citrifolia waste as sources of bioactive compounds - Bintang, I.A.K; Sinurat, A.P; Purwadaria, T (Indonesian Journal of Animal and Veterinary Sciences, 2008)
A study on the use of Zinc bacitracin antibiotic (ZnB) and dried Morinda citrifolia waste as feed additive in broiler ration was conducted. Two hundred and sixteen day old chicks (DOC) was allocated into 4 treatments: control; control + 50 ppm ZnB, and control + M. citrifolia waste at 2 levels (5 and 10 g/kg ration) with 9 replications. Each replicatation consist of 6 birds. The treatments were allocated in a completely randomized design. Variables measured were feed intake, live weight, feed conversion ratio (FCR), percentages of carcass and internal organs (liver, gizard, abdominal fat, and thickness of intestine). The results showed that feed intake ofÂ  M. citrifolia waste was significantly (P<0.05) lower than that of control. Live weight and live weight gain of M. citrifolia waste treatments did not significantly different (P>0.05) from that of control. The use of M. citrifolia waste (5 and 10 g/kg) gave significantly lower (P<0.05) live weight than the use of antibiotic. FCR of M. citrifolia waste 5 g/kg ration and antibiotic was not significantly different (P>0.05), but was significantly lower (P<0.05 ) than that of control and M. citrifolia waste 10 g/kg. Carcass and internal organ percentages were not effected by antibiotic and M. citrifolia waste. Liver percentages with M. citrifolia waste 10 g/kg was significantly (P<0.05) higher and abdominal fat was lower (P>0,05) than that of control, control + antibiotic ZnB and M. citrifolia waste 5g/kg. It is concluded thatÂ  the supplementation of M. citrifolia waste (5 g/kg) could substitute ZnB to improve feed eficiency in broiler ration. Key Words: M. Citrifolia Waste, Performances, Broiler